2018
DOI: 10.1177/1744806918763275
|View full text |Cite
|
Sign up to set email alerts
|

A variant in the SCN10A enhancer may affect human mechanical pain sensitivity

Abstract: Expression of Nav1.8, encoded by SCN10A, can affect pain transmission and thus mediate the human pain phenotype. In the current study, we assessed whether the variant rs6801957, located in the SCN10A enhancer region, may have the potential to affect human pain. Through dual-luciferase reporter assays in 293T cells, we found that the SCN10A enhancer A (Enh-A) increased the activity of the SCN10A promoter (P < 0.05). Additionally, in a cohort of 309 healthy women, mutant rs6801957 A/A was found to have a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a study of mouse hippocampal slices, it was found that the accumulation of some amino acids, including taurine, in cells can increase synaptic potential (27), and studies have also found that the transport process of guanidine compounds in blood cerebrospinal fluid involved in SLC6A6 may be related to neurological disorders in the brain (28). SCN10A is a voltage-gated sodium channel, and many studies on pain have shown that it is closely related to mechanical pain (29). Interestingly, menthol, a natural compound of plant origin, acts as an analgesic by inhibiting the activation of Na ion channels (30), and most current studies have shown that depression and pain symptoms usually coexist and share biological pathways and neurotransmitters (31).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of mouse hippocampal slices, it was found that the accumulation of some amino acids, including taurine, in cells can increase synaptic potential (27), and studies have also found that the transport process of guanidine compounds in blood cerebrospinal fluid involved in SLC6A6 may be related to neurological disorders in the brain (28). SCN10A is a voltage-gated sodium channel, and many studies on pain have shown that it is closely related to mechanical pain (29). Interestingly, menthol, a natural compound of plant origin, acts as an analgesic by inhibiting the activation of Na ion channels (30), and most current studies have shown that depression and pain symptoms usually coexist and share biological pathways and neurotransmitters (31).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in a Ptf1a noncoding region result in adverse itch sensitivity and an increased nocifensive chemical pain response without affecting other somatosensory behaviors Most genome-wide association studies (GWAS) have demonstrated that >90% of disease-associated genetic variants are in noncoding regions (Gallagher and Chen-Plotkin 2018). Examples include a cis-regulatory element for Dmrt3 deleted in patients with gait abnormalities and impaired development of the forebrain (Kubota et al 2018), and single nucleotide polymorphisms (SNPs) in the regulatory region of Scn10a, coding for the NAV1.8 sodium channel, found associated with decreased sensitivity to mechanical pain (Duan et al 2018). Additionally, muta-tions in Ptf1a cis-regulatory regions identified in humans cause pancreatic agenesis (Weedon et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…During the BPPT test, the probe was placed in the middle of the right wrist joint (median nerve). 24 The pain instrument was pressed down, and the pressure reading on the electronic screen was observed. The pressure at the time of the first perceived pain stimulus (blunt-pressure pain-perception threshold, BPPPT) and the pressure at the time of unbearable pain (blunt-pressure pain-tolerance threshold, BPPTT) were recorded.…”
Section: Experimental Pain Measuresmentioning
confidence: 99%